s-Block amidoboranes: syntheses, structures, reactivity and applications. - Stennett, Thomas; Harder, Sjoerd (Chemical Society Reviews, 2016)
Metal amidoborane compounds of the alkali- and alkaline earth metals have in recent years found applications in diverse disciplines, notably as hydrogen storage materials, as reagents for the reduction of organic functional groups and as catalysts and intermediates in dehydrocoupling reactions. These functions are connected by the organometallic chemistry of the MNR2BH3 group. This review focusses on central aspects of the s-block amidoborane compounds - their syntheses, structures and reactivity. Well-defined amidoborane complexes of group 2 metals are now available by a variety of solution-phase routes, which has allowed a more detailed analysis of this functional group, which was previously largely confined to solid-state materials chemistry. Structures obtained from X-ray crystallography have begun to provide increased understanding of the fundamental steps of key processes, including amine-borane dehydrocoupling and hydrogen release from primary and secondary amidoboranes. We review structural parameters and reactivity to rationalise the effects of the metal, nitrogen substituents and supporting ligands on catalytic performance and dehydrogenative decomposition routes. Mechanistic features of key processes involving amidoborane compounds as starting materials or intermediates are discussed, alongside emerging applications such as the use of group 1 metal amidoboranes in synthesis. Finally, the future prospects of this vibrant branch of main group chemistry are evaluated.